FACTORS INFLUENCING THE USE OF ELECTRONIC GOVERNMENT SERVICES IN BRAZIL (REGE Revista de Gestão, 2024)
The purpose of this paper is to explore the secondary data (microdata) from Brazilian “ICT in households and enterprises Survey” in order to understand how the individuals’ use of electronic government services (e-gov) is affected by their location of access to the internet and usage competences of Brazilian internet users. To this end, this research was based on the approach of the capabilities developed by economist Amartya Sen. The procedures concerning processing and data analysis were based on the application of descriptive (univariate and bivariate analysis of frequency) and multivariate statistical techniques (binary logistic regression). The results indicate that the use of e-government services is closely related to the following skills: e-mail usage, e-commerce (search for goods and services) and financial services (consultations). Such skills are favored by Internet access at home and at work, preferred routes to other alternatives such as Internet cafes (public centers providing free access) and tele-centers (public centers with free access). Finally, the article discusses the potential implications of the results of this research in the development of public policies for digital inclusion.